Study of ultrasonic-hydration compound polishing for sapphire optical channel - Qiang Liu; Hongde Wang; Jun Feng; Xiaoqin Zhou; Rongqi Wang; Pengzi Xu (AIP Advances, 2019)
In many significant fields like chemical, biological, medical and optical, many kinds of micro-components are three-dimensionally integrated in the microchips of sapphire. Abrasive flow machining technology can effectively improve the inner surface quality of sapphire microchips and improve their overall performance compared to conventional machining methods. In this paper, a green machining method is proposed for sapphire micro-channel which the modified sapphire layer produced by reacting with high temperature water vapor is removed by ultrasonic vibration abrasives. In this process, a reasonable frequency of 28 kHz and amplitude of 10 um is provided to the workpiece by externally using an ultrasound generator. In order to optimize the critical parameters for the abrasive flow processing, the Taguchi method with four levels L9 orthogonal array is employed to perform the abrasive flow machining orthogonal experiments. The quantitative evaluation on the explicit relationships between surface roughness and processing parameters is analyzed. Finally, the resulted analysis indicates that the machining precision of workpiece is co-determined by the interactive influence of ultrasonic power, machining time and abrasive particle size. The study results can also provide the necessary technical support for the development of ultrasonic abrasive-assisted hydration polishing theory.